National Survey on the importance of sleep in the quality of academic life and mental health of college students in Portugal - Reis, Marta; Ramiro, Lúcia; Paiva, Teresa; Gaspar-de-Matos, Margarida (Sleep Science, 2021)
The academic years are a period of vulnerability when considering sleep problems and mental health. Growing evidence suggests poor sleep patterns are related to impaired academic life and lower psychological well-being. The aim of this study was to explore the importance of sleep habits and report the associations of sleep problems with quality of academic life and different dimensions of mental health (e.g. worries, anxiety, self-regulation and resilience) in a large sample of college students. The HBSC/JUnP data base comprises a representative sample of 2991 college students (n=2203; 73.7% women), aged from 18 to 35 years old (22.43±3.83). Participants socio-demographic characteristics included sex and age. Besides, participants were inquired about sleep duration, characteristics of their sleep habits, questions about quality academic life, namely feeling bored in university, pressure from academic work and academic performance perception and mental health, namely worries, anxiety, self-regulation and resilience. Results showed most young people report an average value for sleep habits (M=4.41; SD=1.46) and that they sleep an average of 7 hours a night. More than half of the young people report either being affected by difficulty falling asleep, showing signs of sleep onset insomnia (67.7%). The conducted analyses indicated that the difficulty falling asleep (having insomnia) was associated with poor/reasonable academic performance perception, higher levels of concerns and anxiety, and lower levels of self-regulation and resilience, thus jeopardizing the mental health of college students. In turn, that characteristics of sleep was also associated with poor sleep habits. In conclusion, this study showed that poor sleep habits were associated with a worse level of academic performance perception and low levels of mental health among college students in Portugal. Universities offer enormous potential as settings to promote sleep-health programs since they can reach many young people who are future-oriented and willing to learn. There is then the need for academic researchers, teaching staff and health professionals working for college students health, to develop and test a wide array of sleep-promoting interventions (e.g., education classes, online programs, adjustment of class time), thus preventing negative secondary outcomes.
Keywords: Sleep; Quality of academic life; Mental Health; College students; Portugal